Topsoil removal through scarification improves natural regeneration in high‐graded Nothofagus old‐growth forests. Issue 2 (30th August 2017) - Soto, Daniel P.; Puettmann, Klaus J.
Abstract: High grading by removing the majority of trees with superior timber quality has led to loss of productivity and biodiversity in forests. Typically, after high grading, little attention is given to tree regeneration. Thus, undesirable understorey vegetation often dominates for a long time, leading to stagnation in forest recovery and so‐called arrested succession. In such settings, managing understorey vegetation using topsoil removal through scarification has been proposed as a restoration tool to encourage tree regeneration. We investigated the effectiveness of topsoil removal as a restoration technique in high‐graded Nothofagus old‐growth forests in the Chilean Andes. In these forests, high grading often leads to understories being dominated by dense thickets of native bamboo, Chusquea culeou . These understorey conditions typically delay succession by preventing tree regeneration. T ‐tests were used to compare vegetation development in areas with topsoil removal against those without. Nonparametric multiplicative regression was used to investigate which environmental variables were mainly related to regeneration of different plant groups (short‐ and long‐lived, early‐ and late‐seral tree species) and C. culeou abundance in areas with and without topsoil removal. Topsoil removal improved the regeneration of early‐seral tree species and constrained C. culeou . In areas without topsoil scarification, higher abundances of C. culeou were reflected in a higher transmitted radiation and litter cover. In these areas, the presence of early‐seral tree species was related to higher soil water content and transmitted radiation. However, topsoil removal altered these response patterns for early‐seral trees. For instance, the interaction between higher soil water content and more exposed mineral soil was reflected in a higher likelihood of finding early‐seral tree seedlings. Synthesis and applications . Topsoil removal was a successful restoration tool for overcoming arrested succession in Nothofagus old‐growth forests in the Chilean Andes by encouraging the regeneration of early‐seral trees in high‐graded forests. Contrasting environmental conditions of pre‐ and post‐topsoil removal allowed insights into the processes and mechanisms responsible for forests with arrested succession and for succession progression. This understanding provides guidance regarding the range of conditions under which topsoil removal can be used as a successful restoration practice. Abstract : Topsoil removal was a successful restoration tool for overcoming arrested succession in Nothofagus old‐growth forests in the Chilean Andes by encouraging the regeneration of early‐seral trees in high‐graded forests. Contrasting environmental conditions of pre‐ and post‐topsoil removal allowed insights into the processes and mechanisms responsible for forests with arrested succession and for succession progression. This understanding provides guidance regarding the range of conditions under which topsoil removal can be used as a successful restoration practice.